Critical analysis of the thermodynamics of reaction kinetics (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Our objective is to show the weakness of the recent thermodynamics of chemical reactions. We show that such a thermodynamic theory of chemical reactions, which could be similar to the generalized Onsagers theory in thermodynamics, is not reality at the moment.